Brokering Culture and Power in a Media-Driven World: Parents of Adolescents in Northern Thailand. (September 2019) - McKenzie, Jessica; Rooney, Joseph; Stewart, Cassandra; Castellón, Rachel; Landeros, Cristina; Willis, Emma
Exposure to modern media alters cultural values and individual identities. Little is known, however, about whether and how media use alters cultural socialization processes in family relationships. In this study, 20 urban Thai parents of adolescent children took part in individual interviews in which they discussed media use in their families. Thematic analysis of interview data indicates that adolescents act as cultural brokers for their parents in a media-driven culture, and that this brokerage engenders adolescent agency, power, and the renegotiation of traditional age-based hierarchies in the Thai context. Data also indicate that parental power and authority are maintained and reasserted by way of parents placing restrictions on adolescent media use and mobilizing their children's technological desires as opportunities to teach culturally salient lessons about necessity—a value that reflects central tenets of the late Thai King Bhumibol's Sufficiency Economy and of Buddhism's Four Noble Truths. Findings suggest that media use can both transform and maintain traditional cultural values and family dynamics in northern Thailand. More broadly, this study carries implications for the psychological science of globalization by applying the concept of cultural brokerage to communities undergoing rapid technological change.